The study of the effects of digital media applications in cross-cultural communication in the construction of cultural identity - Meng Yao (Acta Psychologica, 2025)
Background: This study investigates how digital media usage impacts cultural identity construction across diverse cultural contexts, focusing on the mediating roles of technological affordances, symbolic representation, and social engagement. Methods: The design was a mixed methods sequential explanatory design. A structured survey was used to collect quantitative data on variables related to digital media usage as well as variables related to cultural identity strength and intercultural communication. Five hundred participants were recruited from a stratified random sample of different cultural backgrounds. Descriptive statistics, t-tests, multiple regression, and Structural Equation Modelling (SEM) were used to analyse the quantitative data using R version 4.4.2. In the qualitative phase, 30 participants were selected for semi-structured interviews to provide deeper insights into the quantitative findings using thematic analysis in NVivo. Results: Our analysis identified significant predictors of cultural identity construction: technological affordances (β = 0.38, p < 0.001), symbolic representation (β = 0.42, p < 0.001), and social engagement (β = 0.30, p < 0.001). Mediation effects were observed: symbolic representation mediated the relationship between technological affordances and identity construction (β = 0.16, p < 0.001), and social engagement mediated symbolic representation's effect on identity (β = 0.36, p < 0.001). t-tests showed cultural group differences in media usage and identity strength. Conclusion: The findings suggest practical applications for educational, cultural preservation, and policy initiatives, emphasizing the potential of digital platforms in promoting global intercultural dialogue.